Laboratorial Investigation and Simulation Test for Spontaneous Combustion Characteristics of the Coal Waste under Lean-Oxygen Atmosphere. Issue 1 (2nd January 2020) - Tang, Yibo; Wang, Huae
ABSTRACT: As a typical solid waste, coal gangue is highly susceptible to spontaneous combustion. Conventionally, method for controlling spontaneous combustion of coal gangue is to inhibit the oxidation and self-heating of gangue by utilizing soil covering to isolate the gangue from oxygen. Using various methods, such as FTIR, TG/DSC, program heating and physical simulation, the change of spontaneous combustion characteristics (SCCs) of coal gangue under 3–21.0% O2 was explored. Results show that lean-oxygen significantly decrease the heat release from coal gangue during low-temperature oxidation, inhibit the generation of O-containing functional groups, and postpone the appearance of characteristic temperature points on the thermogravimetry (TG) curve. Between 30 and 140°C, the activation energy during oxidation of coal gangue ranges 29.85–47.72 KJ/mol. The oxygen consumption rate (OCR) of coal gangue showed a nonlinear positive correlation with O2 concentration. Field simulation test showed that after coal gangue was stacked for 60 d, the gangue temperature rose to 39.6°C. After covering the soil, the temperature data increased slowly. However, oxidation of coal gangue was not completely inhibited even the lowest O2 concentration reduced to 18.35%. In conclusion, investigation in the paper provides further guidance for reducing risk of gangue self-ignition.